Enhancement effects of chicken interleukin-2 on immune responses of H5 subtype avian influenza virus vaccines - LIU Yan; YOU Zhen-qiang; XU Jian; ZHENG Jiang-tao; YU Lian (浙江大学学报. 农业与生命科学版)
In order to boost immune response of conventional vaccines, investigation was made on immunoadjuvants-eukaryotic expression plasmid (pCI-IL-2) and recombinant chicken IL-2 (rChIL-2) expressed in E. coli. The adjuvants were coadministrated with H5 subtype inactivated avian influenza virus (AIV) vaccines. Non-immunized commercial chickens were injected initially at 25-day-old and boosted 2 weeks later. Proliferation responses of chicken periphery blood lymphocytes were measured by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenylt-etrazolium bromide (MTT) assay and the titers of specific antibodies to the H5 vaccine by hemagglutinin inhibit (HI) test. As the results revealed, the cellular and humoral immune responses were significantly enhanced in the groups co-immunized with pCI-IL-2 or rChIL-2 compared to the group inoculated with H5 vaccine only. No significant difference were found between the two co-immunized groups (P<0.05). Peak values of MTT and HI in the rChIL-2 coinoculated group were attained 4 weeks after initial inoculation, which was earlier than the group coinoculated with pCI-IL-2. These results presented evidence that both pCI-IL-2 and rChIL-2 could be employed as effective immunoadjuvant to conventional vaccines against avian influenza.